THE PROCESSES OF PROCUREMENT PRODUCTION MATERIALS AND SEMI-FINISHED PRODUCTS IN THE COMPANY ZF SACHS TRNAVA A.S. (Perner's Contacts, 2013)
The process of procurement of production materials and semi-finished products belongs to the process supply chain logistics, which is essential to ensure the production schedule. It is necessary to ensure that production material was supplied at the right time, at the right place and in the right quality. Purchasing and supply mainly related with the determining and ensuring needs and material resources for the effective operation of the production process. Ensuring of purchase and continuous supply during the manufacturing process is extremely challenging task, because often regards hundreds or even thousands of items specified to scheduling daily production tasks. To handle this task decisive manner affects the economy of the production process.